Effectiveness of SEMA No. 2 of 2023 Regarding Interfaith Marriage in Indonesia - Razak, Abd. Rahman; Gassing, Qadir; K, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses the condition of interfaith marriages in Indonesia after the emergence of SEMA No. 2 of 2023. Before the emergence of SEMA, interfaith marriage was something that was often debated by academics because there were no regulations that clearly regulated legal interfaith marriage. The emergence of SEMA is considered to provide legal certainty to support the implementation of Law no. 1 of 1974 so that marriage is based on the provisions of each religion. The SEMA is considered effective in closing the way for interfaith marriages, but its reach is limited to the judicial environment, while the reality in society is still happening even after the SEMA was established. This is because there is still a gap, namely through registration at the Disdukcapil Office. So it is considered necessary to harmonize norms in a number of laws and regulations such as the Marriage Law and the Administering Law. This research uses library research methods. Research data was obtained through literature study, namely reading and analyzing documents relevant to this research.